2023
DOI: 10.1002/cae.22654
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the differences and evolution of college students' computational thinking in programming learning through data analysis

Wei Zhang,
Xinyao Zeng,
Panpan Li
et al.

Abstract: Programming has received extensive attention for the embodiment of computational thinking (CT) skills. However, the lack of in‐depth research on the characteristics of college students' CT skills in text‐based programming learning has resulted in the unknown distribution characteristics and evolution patterns of their CT skills, which cannot effectively constitute an effective tracking analysis of their CT skills, thus affecting the cultivation of creative thinking and problem‐solving skills for them. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Perkembangan teknologi front-end web, seperti HTML 5 dan CSS 3, telah membuat pemrograman front-end menjadi lebih profesional dan menantang, sehingga menekankan perlunya pelatihan dan pengembangan keterampilan yang komprehensif di bidang ini ("Research and Application of Web Front-End Development Micro-Speciality Curriculum System in Higher Vocational Colleges," 2021). Penelitian telah menunjukkan bahwa intervensi dan program pembelajaran keterampilan dapat secara signifikan meningkatkan pemikiran kritis, keterampilan pemecahan masalah, dan pemikiran komputasi mahasiswa dalam pembelajaran pemrograman (W. Zhang, 2023). Selain itu, penerapan metode rendering formulir dinamis untuk kerangka kerja multi-front web telah diidentifikasi sebagai area kritis untuk perbaikan, menyoroti perlunya strategi belajar mengajar yang efektif dalam pengembangan front-end (Y.…”
Section: Pendahuluanunclassified
“…Perkembangan teknologi front-end web, seperti HTML 5 dan CSS 3, telah membuat pemrograman front-end menjadi lebih profesional dan menantang, sehingga menekankan perlunya pelatihan dan pengembangan keterampilan yang komprehensif di bidang ini ("Research and Application of Web Front-End Development Micro-Speciality Curriculum System in Higher Vocational Colleges," 2021). Penelitian telah menunjukkan bahwa intervensi dan program pembelajaran keterampilan dapat secara signifikan meningkatkan pemikiran kritis, keterampilan pemecahan masalah, dan pemikiran komputasi mahasiswa dalam pembelajaran pemrograman (W. Zhang, 2023). Selain itu, penerapan metode rendering formulir dinamis untuk kerangka kerja multi-front web telah diidentifikasi sebagai area kritis untuk perbaikan, menyoroti perlunya strategi belajar mengajar yang efektif dalam pengembangan front-end (Y.…”
Section: Pendahuluanunclassified
“…Research by (Chai et al (2020) and highlighted the importance of AI education and literacy in shaping students' perceptions and attitudes towards AI, emphasizing the need to incorporate AI-related content into the educational curriculum. Research on ChatGPT in educational settings has concluded that it is a generative artificial intelligence medium that is rapidly gaining global recognition owing to its wide range of potential benefits (Wu et al, 2024;W. Zhang, 2023).…”
Section: Introduction *mentioning
confidence: 99%